Using genre based approach and comics to improve reading comprehension (2023)
Reading comprehension is an important skill on EFL teaching process, this skill represents understanding of text. This study conducted and action research to explore how the use of genrebased approach and comics encouraged 7th grader’s reading comprehensions skill in a public school in Monteria, Cordoba. This qualitative study uses different techniques to collect data and create the intervention plan, following the action research cycle. Findings of this research demonstrate that students positively improve their reading skill after the application of Genre Based approach and comic, students were able to make critical inferences of the comics analyzed during each stage of the GBA: Modeling, Joint construction, and independent construction of the text. The results demonstrate that students not only improve this skill, also the obtain an enhance o their writing skill, vocabulary acquisition and engagement during English classes. This study demonstrates the importance of applying innovating strategies that engaged students with this important skill.